Economic Theory and Financial Policy : Selected Essays of Jacques J. Polak, 1994-2004. (International Monetary Fund, 2004)
This paper describes the essence of the Bretton Woods conference. The Bretton Woods conference was one of a number of inter-allied conferences in the later part of World War II that led to the creation of a new international organization. The point of this paper is not to defend the Bretton Woods agreements of 1944, but rather to stress the continuity of the IMF's mandate to promote monetary cooperation among countries. The paper also draws lessons for the future from the work of the IMF in the 1960s and 1970s.